2015
DOI: 10.1161/hypertensionaha.115.05544
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Identification of a Novel Pathway of Blood Pressure Regulation Involving Hexadecanedioate

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
80
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(94 citation statements)
references
References 38 publications
5
80
1
4
Order By: Relevance
“…41,42 Graessler et al 41 reported altered blood plasma levels of acylalkyl-phosphatidylcholines in hypertensive German men, relative to the control group of normotensive men. Notably, identified acylalkyl-phosphatidylcholines (C36:4, C36:5, C38:4-C38:6) were highly unsaturated, as the 3 identified phosphatidylcholines metabolites in this study which may be beneficial to enhance membrane fluidity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…41,42 Graessler et al 41 reported altered blood plasma levels of acylalkyl-phosphatidylcholines in hypertensive German men, relative to the control group of normotensive men. Notably, identified acylalkyl-phosphatidylcholines (C36:4, C36:5, C38:4-C38:6) were highly unsaturated, as the 3 identified phosphatidylcholines metabolites in this study which may be beneficial to enhance membrane fluidity.…”
Section: Discussionmentioning
confidence: 99%
“…However, none of the metabolites, reported by Graessler et al, 41 were associated with incident hypertension in this study, suggesting differences in metabolite composition of individuals with incident and prevalent hypertension. Recently, of 280 metabolites, 15 metabolites were identified by Menni et al 42 to be independently associated with BP. However, of identified metabolites, only hexadecanedioate, a dicarboxylic acid, showed concordant association with BP in 2 replication cohort (KORA and Hertfordshire).…”
Section: Discussionmentioning
confidence: 99%
“…Metabolomics is a new high-throughput technology that measures endogenous metabolites in cells, tissues and other biosamples such as blood, urine and saliva (15) . These metabolites provide a direct signature of the biochemical activities of the individual at a particular time, reflecting the metabolic effects of nutritional intake, physical activities and environmental exposures as well as the biological pathways associated with diet-related diseases including obesity, CVD and type 2 diabetes (16)(17)(18)(19) . Metabolites have been proven to be of use in nutritional research and novel dietary biomarkers within the metabolome have been identified (20)(21)(22)(23) .…”
Section: Metabolomicsmentioning
confidence: 99%
“…As yet there are, however, only limited data available that specifically address hypertension, in part because of the difficulties disentangling blood pressure from its consequences including target organ damage. Nevertheless, some metabolites such as hexadecanedioate have been found to be differentially regulated in hypertension [28] and the potential of proteomics to impact on cardiovascular health and disease has recently been defined [29]. In specific hypertensive conditions such as pre-eclampsia a wealth of proteomic and metabolomic data are available that provide some insights into the pathogenesis that could also inform our understanding of essential hypertension and other vascular diseases [30][31][32].…”
Section: Genetic Aspects and "Omics"mentioning
confidence: 99%